2019
DOI: 10.1074/jbc.ra119.008765
|View full text |Cite
|
Sign up to set email alerts
|

Nonnative structure in a peptide model of the unfolded state of superoxide dismutase 1 (SOD1): Implications for ALS-linked aggregation

Abstract: Dozens of mutations throughout the sequence of the gene encoding superoxide dismutase 1 (SOD1) have been linked to toxic protein aggregation in the neurodegenerative disease amyotrophic lateral sclerosis (ALS). A parsimonious explanation for numerous genotypes resulting in a common phenotype would be mutation-induced perturbation of the folding freeenergy surface that increases the populations of high-energy states prone to aggregation. The absence of intermediates in the folding of monomeric SOD1 suggests tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 51 publications
1
7
0
Order By: Relevance
“…The misfolding and aggregation of superoxide dismutase 1 (SOD1) are associated with the fetal neurodegenerative disease amyotrophic lateral sclerosis (ALS). Recent X-ray crystallographic studies have captured a corkscrew-like oligomeric species formed by the amyloidogenic segment residues 28–38 of SOD1 (with the sequence KVKVWGSIKGL). , This segment is the core fragment of the SOD1 protein and has been reported to play a critical role in SOD1-mediated toxicity . The physiological relevance of the oligomeric species formed by SOD1 28–38 calls for the dynamic studies to follow its evolution, which will provide important insights into the aggregation mechanism of the full-length protein. , Particularly, it is unknown whether the corkscrew-like oligomer is an on-pathway intermediate or an off-pathway by-product.…”
Section: Introductionmentioning
confidence: 99%
“…The misfolding and aggregation of superoxide dismutase 1 (SOD1) are associated with the fetal neurodegenerative disease amyotrophic lateral sclerosis (ALS). Recent X-ray crystallographic studies have captured a corkscrew-like oligomeric species formed by the amyloidogenic segment residues 28–38 of SOD1 (with the sequence KVKVWGSIKGL). , This segment is the core fragment of the SOD1 protein and has been reported to play a critical role in SOD1-mediated toxicity . The physiological relevance of the oligomeric species formed by SOD1 28–38 calls for the dynamic studies to follow its evolution, which will provide important insights into the aggregation mechanism of the full-length protein. , Particularly, it is unknown whether the corkscrew-like oligomer is an on-pathway intermediate or an off-pathway by-product.…”
Section: Introductionmentioning
confidence: 99%
“…Given that the results indicate that the monomer is the likely precursor that triggers the downstream oligomerization cascade, ,, understanding the G93A SOD1 structural changes from native dimer to monomeric species may shed light upon the molecular basis of the aggregation mechanism. In the following study, we focus on the elucidation of the unfolding events and localization of the regions associated with the unfolding of G93A SOD1 induced by TFE.…”
Section: Resultsmentioning
confidence: 99%
“…Furukawa et al identified a protease-resistant core structure within various fALS-inducing mutant SOD1 aggregates and found three regions (amino acids 1–30, 90–120, and 135–153) that are likely to form a scaffold core for the aggregates. Matthews and co-workers recently reported that the C-terminus of SOD1 (loop VII-β8 regions) is involved in a non-native interaction with a disordered N-terminus, a non-native intramolecular structure that may provide a nucleation site for ALS aggregations. In addition, Kumar and co-workers, using molecular dynamics simulations, showed that SOD1 undergoes partial unfolding of β-strands 4, 5, and 6 before TFE-induced aggregation.…”
mentioning
confidence: 99%
“…The C-terminus of SOD1 would have ample opportunity to collapse on itself and introduce chain friction for both reactions. Although the marginal stability of the Loop VII-b8 peptide to denaturant appears to challenge this explanation for friction-limited unfolding, the presence of the TSE in the full-length protein and high concentrations of viscogen make comparisons ambiguous and highlight the limitations of peptide models for unfolded proteins (25).…”
Section: Internal Friction In Sod1mentioning
confidence: 99%
“…Loop IV binds the zinc ion, whereas Loop VII, the electrostatic loop, serves to support Loop IV and guides the anionic substrate to the redox-active copper ion. A recent peptide dissection analysis of SOD1 from our lab demonstrated that the 35-residue C-terminal peptide, containing Loop VII and b8, folds on itself to bring the polar and charged N-terminus and the nonpolar C-terminus into a nonnative juxtaposition (25). This interaction cannot exist in the disulfide-containing form of SOD1, in which C146 in b8 is covalently linked to C57.…”
Section: Introductionmentioning
confidence: 95%